Software Systems in Implementation of Process Safety at Chemical Process Industry - Yew, Kwang Hooi; Hassan, M.F.; Azmi , Mohd Shariff; Hanida, Aziz; Sujendran, Suppiah (2014)
Software systems have been used in chemical industry process safety operation and design to improve its efficiency. This paper provides a brief review and analysis of the state of the art and impacts of software systems in process safety. A study was carried out by interviewing personnel in charge of process safety practices in the Malaysian chemical process industry and digging into literature of technology for process safety. This article explores the functional and operational characteristics of software systems for safety and attempts to categorize the software according to its level of impact in the management hierarchy. The study contributes to better understanding of the roles of Information Communication Technology in process safety, the future trends and possible gaps for research and development.